The school bereavement toolkit : a practical guide to supporting children - Palmer, Jacquie (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Practical and accessible, this guidebook is designed to help staff in schools support bereaved children in their care. Providing information and guidance on practical issues around bereavement and indicating some of the issues that might require extra thought or assistance, this book makes accessing relevant information as easy and quick as possible. When busy school staff are faced with a bereaved child the prospect can be daunting. What do I say? What can I do? Will I make it worse? Have I got time to do this? This book is a toolbox to give staff confidence in helping bereaved young people. Information is easily accessed and simple to use, giving staff quick and practical help. There are sections on what will help and what will not, also included are and photocopiable worksheets and tools to aid children and young people to explore their grief, as well as how school communities can share the news and manage an initial response. With age appropriate guidance to help school staff working in both primary and secondary settings, this key guide provides quick to access information for those not trained in child bereavement to help individual children or whole classes following a loss"--
Introduction -- Basic procedures on hearing the news and in the longer term -- How a bereaved child might be feeling -- Considerations when talking to a bereaved child -- Interventions in the classroom -- Answering difficult questions -- Helping classmates support their grieving friend -- When a child in the class dies -- When a bereavement needs more support -- Support for the carers -- Helpful organizations.
"A Speechmark Book" -- Cover.
Keywords: Bereavement in children; Loss (Psychology); Social work with children; FAMILY & RELATIONSHIPS / Death, Grief, Bereavement; EDUCATION / Counseling / General; EDUCATION / Elementary